New records of little known pyraloid moths (Lepidoptera: Pyraloidea) from different regions of Ukraine - Yepishin, Viktor; Khalaim, Yevhenii; Demyanenko, Serhii; Govorun, Oleksandr; Novytskyi, Sergiy; Tsykal, Serhii (Zootaxa, 2025)
This paper presents new reports of 42 Pyraloidea species from Ukraine, comprising both regional and country-level novelties. Two species are recorded in Ukraine for the first time: Apomyelois cognata (Staudinger, 1871) (Phycitinae) from Luhansk region and Herpetogramma licarsisalis (Walker, 1859) (Spilomelinae) from Odesa region. Another three species are found for the first time in mainland Ukraine: Tsaraphycis mimeticella (Staudinger, 1879) (Phycitinae) from Luhansk region, Nyctegretis ruminella De la Harpe, 1860 (Phycitinae) from Zaporizhzhia region, and Hydriris ornatalis (Duponchel, [1832]) (Spilomelinae) from Odesa region. All of these were previously known only from Crimea. Additionally, 35 other species are recorded from different regions of Ukraine for the first time. Adults and genitalia of several rare or interesting species are illustrated. Some inaccuracies regarding misidentification and misprint made in previous publications are corrected here.